Post-operative sleep and activity patterns in critically ill children after cardiac surgery - Hassinger, Amanda B.; Berger, Jessica A.; Aljohani, Othman A.; Kudchadkar, Sapna R. (Progress in pediatric cardiology, 2023)
Children with congenital heart disease often have medical and surgical complexity and prolonged and complicated recovery time in the intensive care unit. Limited data are published describing sleep duration, timing, and quality in this population. This study was performed to describe sleep and activity patterns of children with congenital heart disease in the immediate post-operative period. This was a secondary analysis of an observational trial of children (0-18 years) who underwent cardiac surgery and had accelerometer data. The primary outcome was the daytime activity ratio estimate (DARE), defined as the proportion of activity that occurred during the daytime hours. Secondary outcomes were sleep quality, including sleep fragmentation index and sleep duration. In total, 130 subjects with 794 hospital days of sleep data were included. Median age was 2.9 years (IQR 0.6-9.9). 83 (63.8%) were males, and 51 (39%) had cyanotic lesions. 35 subjects (26.9%) underwent single ventricle repairs. Average nighttime activity levels were higher than normal in all subjects with an average DARE of 61.1% (±5), normal 75%. Variables independently associated with DARE were total daily sleep time (p=0.005) and total benzodiazepine dose in mcg/kg (p=0.006). Almost half of the subjects had inadequate total sleep time (60, 46%). There was a significant decrease in total sleep time and proportion of subjects with adequate sleep duration in the lower age categories. For every year increase in age, the odds of adequate sleep increased by 27%, p<0.001. Children post cardiac surgery have higher than normal levels of nighttime activity and almost half do not meet the recommended daily hours of sleep. Infants under 1 year of age may be at a higher risk of inadequate sleep. Exposure to benzodiazepines may also affect the balance between daytime and nighttime sleep patterns after cardiac surgery. •Limited sleep data exist about children with congenital heart disease after cardiac surgery•Almost half of children do not get adequate daily sleep during recovery from cardiac surgery•Up to 40% of daily activity occurs at night in children after cardiac surgery•Children under one year old are at higher risk for sleep-wake cycle disruption